Burn Injuries in Primary School Children: A Multicenter Epidemiological Study Between 2009 and 2023 - Abdolkhalegh Keshavarzi; S. Yasamin Parvar; Mandana Goodarzian; Aram Maaroufi; MReza Goodarzian; Gholam Reza Motazedian; Mitra Zardosht (Health Science Reports)
ABSTRACT Background Burns in pediatric populations lead to severe cosmetic and traumatic injuries, impacting their future. Understanding burn causes and predisposing factors is essential for prevention, particularly in primary school‐aged children who are beginning their social and educational lives. Aim This study evaluates the epidemiology and etiologies of burn injuries among primary school children from 2009 to 2023. Methods This retrospective study assesses burn data, including age, home place, burn etiology, final status, injury location, injury type, TBSA (Total Body Surface Area), and LOS (Length of Stay). Data were extracted from the burn research data center and analyzed using univariate and multivariate logistic regression analyses to identify independent survival predictors in children aged 7–14 years over a 14‐year period admitted to the Amir‐al‐Moemenin and Ghotb al‐Din‐e‐Shirazi burn hospitals. Results Of the 8510 patients admitted, 571 were aged 7–14 years, with a male‐to‐female ratio of 2.2 and a mean age of 10.1 years. Flame burns were the most common (51.7%), with winter being the peak season (27.7%). Accidental burns (p = 0.003) in outdoor places (p < 0.001) and urban areas were significantly more common among males. Females had a significantly higher mean TBSA%. Over 85% of patients were released or discharged, with a mortality rate of 13.2%. TBSA% in flame burns and LOS in chemical and electrical burns were significantly higher (p < 0.001). Univariate analysis identified age, male gender, accidental occurrence, rural living, TBSA%, and LOS as significant predictors of survival. Multivariate analysis confirmed TBSA% and LOS as strong survival predictors. Conclusion Flame burns are the primary etiology, occurring mostly outdoors, in younger males living in urban areas, and predominantly accidental. Further studies in various pediatric groups are necessary to reduce the financial, educational, and health complications associated with burns.